The Right to Reading Materials - Purwanda, Sunardi; Dewi, Mira Nila Kusuma; Miqat, Nurul (Universitas Brawijaya, 2025)
Article 13(2) of the ICESCR contains the provision of the right to education and freely access educational affairs, including reading materials. But can we establish the right to reading materials as the citizens’ rights? Does it apply to a certain group or all people without exception? And, under what conditions is the applicability of the right attached? Previous research articles by Andina (2011), Rahajaan (2012), Affandi (2017), Purwanda & Syahril (2021), Jacobs (2013), Hartsfield & Kimmel (2021) have not specifically reviewed the status of the right to reading materials, highlighting whether the provision of reading materials by the state has significance to the protection and recognition of rights and whether the right applies only to a group of people or all people without exception, as well as how the enforceability of the right is attached to citizens. The sophistication of this this sociolegal research uses an interdisciplinary approach in law, lies in the provision of reading materials by the state is a right that cannot be separated from the human right and the need for the state to provide reading materials as a form of protection and recognition of the citizen’s rights. The state is obliged to provide and protect the right to reading materials for its citizens as a form of protection and recognition of citizens' rights. Legal protection of citizens' rights to reading materials requires legal fulfilment by the state as part of the right to enjoy or obtain education (right to education).